RESEARCH INTO THE MODERN ECONOMIC DEVELOPMENT OF THE CHEMICAL INDUSTRY IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. Many developed countries regard chemical industry as a key branch of economy having a significant impact on the general economic situation.Presently, the chemical industry, which is highly science-intensive and one of the most actively promoted in the world market, is largely on a par with mechanical engineering.Despite numerous scientific papers dealing with the peculiarities, obstacles and prospects of the chemical industry’s development in Ukraine, the issues related to the peculiarities of the chemical enterprises’ development in the conditions of a long-term economic crisis still require further investigation.The purpose of the article is to analyze the peculiarities of the Ukrainian chemical enterprises’ development under the conditions of a political and economic crisis.Results The adverse conditions, which the Ukraine’s industry, namely basic chemistry and metallurgy, currently faces, have primarily resulted from the impact of the global financial crisis of 2008-2009 and internal problems that the country has encountered since the beginning of 2014, especially due to the hostilities in the east.Chemical production in Ukraine, unlike that in other countries of the world, is based mainly on the outdated technologies that have remained since the Soviet Union times, which leads to the increased resource consumption and reduces its competitiveness in the world market; this further prevents the reduction of costs and innovative production in the sectors of the economy that consume chemical products.A characteristic feature of the chemical industry is a very complex production structure, comprising approximately 200 interconnected industries, which are divided into four major groups: mining, chemical production, pharmaceuticals production, rubber and plastics production.Ukraine ranked 13th in comparison with EU countries in terms of exports of chemical products, and 8th in terms of imports.During the period under review, two positive points in the dynamics of the rating of exports of chemical products in Ukraine can be identified: in 2011, Ukraine managed to rise by one step in the list in terms of exports of chemical products, and in 2017, in the conditions of crisis, domestic chemical enterprises managed to adapt and stabilize the situation.The linear rate of decline in exports of chemical products is US $ 403.1 million per year, while the decrease in imports of chemical products occurs at the rate of US $ 168.3 million per year.In 2018, production of chemical products - basic chemistry and pharmaceuticals in the aggregate occupy the seventh place in the composition of Ukraine’s industry following the sales and the supply of energy, food production, metallurgy, mining, machine building, production of coking coal and oil refining.During the period under review, the structure of the chemical production has gradually changed: since 2011, the share of basic chemistry was decreasing, whereas the share of pharmaceuticals was simultaneously increasing.In 2018 compared to 2017, the share of pharmaceutical products decreased slightly while the share of the production of basic chemical products increased.Positive dynamics of GDP (in actual prices) and the volume of the chemical products sales in Ukraine for the period 2010-2018 is primarily due to the increase in the overall price level in the country's economy.By region, the most sensitive to the changes in the chemical markets would be the regions with the highest concentration of chemical industries.In 2017, the share of the chemical industry in Ukraine is the highest in the Dnipropetrovsk region (26.81%) and the lowest in the Chernivtsi region (0.16%).The dynamics of the chemical products sales volumes has been analyzed with the regions leaders and outsiders in chemical production having been identified.The impact of the crisis on the chemical industry has been determined based on the comparison of the main performance indicators of chemical enterprises in the pre-crisis 2013 and 2015 - the second year since the onset of the economic crisis.Conclusions. The study found that one of the main obstacles to the development of the industry is outdated technological equipment, which cannot be overcome due to the lack of own funds and an unsatisfactory investment climate in the country.Compared with the production of basic chemical products, pharmaceutical production has had better results, which appears natural, since the age group of the population of retirement and pre-retirement age in Ukraine - the main buyers of medicines - is dominant.As a result of the study, the main problems that currently impede the development of the chemical industry have been identified and the main ways of the industry’s development have been proposed.The prospects for the development of the chemical industry are related to the following: improvement of the structure of the chemical enterprises’ resource potential, adapting it to the requirements of time; increasing innovation activity and investment attractiveness; state stimulation of the process of technical and technological updating of production funds and innovation activity; raising the level of mechanization and automation at all stages of the production process; reconstruction of a number of chemical enterprises and closing of outdated and unprofitable ones.
Keywords: chemical industry, activity of chemical enterprises, development prospects of the industry, crisis, dynamics indicators, development trends